Nonlinear finite element model for the novel mechanical beam-column joints of precast concrete-based frames. (September 2017) - Nzabonimpa, J.D.; Hong, Won-Kee; Kim, Jisoon
Highlights: Novel mechanical beam-column joint for precast concrete moment frames are presented. Numerical models for the proposed joint accurately predicted the behavior of the joint. Failure modes of the proposed joint were studied based on FEM models. Extensive experimental investigations were performed to validate the proposed joint. A variety of parameters including concrete damage and dilation angle were investigated. Abstract: The aim of this study is to present a detailed nonlinear finite element study to reproduce the experimental response of new mechanical beam-column joints of precast concrete based frames. Nonlinear finite element model based on concrete damaged plasticity is proposed for precast concrete beam-column jointed by mechanical metal plates. The proposed model accounts for surface-to-surface contact property to define metal plates contacted with concrete and nuts threaded with rebar end. Nonlinear finite element analyses of mechanical beam-to-column joints under static loadings were undertaken to uncover their failure modes including the deformations of beam end plates and the concrete damage of the novel mechanical connections that create rigid joint. Experimental investigations of three full-scale test specimens were performed to explore the structural behavior of the fully-restrained moment connection by identifying the parameters. The results obtained from analytical studies demonstrated good agreement with the experimental results, demonstrating that our finite element model can accurately predict the structural behavior of the proposed beam-to-column joint connection despite its complex geometric configuration the and the inherent complexity of the proposed beam-to-column mechanical joint. FE models also present attractive alternatives to high-cost experiments for the proposed mechanical joint.